Coherence Time Extension by Large-Scale Optical Spin Polarization in a Rare-Earth Doped Crystal - Sacha Welinski (American Physical Society, 2020)
Optically addressable spins are actively investigated in quantum communication, processing, and sensing. Optical and spin coherence lifetimes, which determine quantum operation fidelity and storage time, are often limited by spin-spin interactions, which can be decreased by polarizing spins. Spin polarization can be achieved using optical pumping, large magnetic fields, or mK-range temperatures. Here, we show that optical pumping of a small fraction of ions with a fixed-frequency laser, coupled with spin-spin interactions and spin diffusion, leads to substantial spin polarization in a paramagnetic rare-earth doped crystal, ^{171}Yb^{3+}∶Y_{2}SiO_{5}. Indeed, more than 90% spin polarization has been achieved at 2 K and zero magnetic field. Using this spin polarization mechanism, we further demonstrate an increase in optical coherence lifetime from 0.3 ms to 0.8 ms, due to a strong decrease in spin-spin interactions. This effect opens the way to new schemes for obtaining long optical and spin coherence lifetimes in various solid-state systems such as ensembles of rare-earth ions or color centers in diamond, which are of interest for a broad range of quantum technologies.